Increasing light physical activity helps to maintain cognitive function among the community‐dwelling oldest old population: a cross‐sectional study using actigraph from the Arakawa 85+ study. Issue 8 (22nd June 2020) - Suzuki, Kouta; Niimura, Hidehito; Kida, Hisashi; Eguchi, Yoko; Kitashima, Chiho; Takayama, Midori; Mimura, Masaru
Abstract : Aim: To investigate the influence of replacing sedentary time with physical activity on cognitive function using an isotemporal substitution model in a population of community‐dwelling oldest old. Methods: This cross‐sectional study included residents of the Arakawa ward, Tokyo, who were part of a prospective cohort from the Arakawa 85+ study. We measured physical activity in 136 participants using a triaxial actigraph. Cognitive function was measured using the Addenbrooke's Cognitive Examination‐III and participants were divided into a "cognitive decline group" (Addenbrooke's Cognitive Examination‐III ≤88) and "cognitive maintain group" (Addenbrooke's Cognitive Examination‐III ≥89). Physical activity was divided into three categories: sedentary behavior (≤1.5 metabolic equivalents), light physical activity (>1.5 to <3.0 metabolic equivalents), and moderate‐to‐vigorous physical activity (≥3 metabolic equivalents). Using an isotemporal substitution approach, we applied multiple logistic regression analysis to demonstrate the association between cognitive function and replacing 30 min/day of sedentary behavior with an equal period of light physical activity. Covariates included age, education and the Center for Epidemiologic Studies Depression Scale. Results: Our findings showed that in men, replacing 30 min of sedentary behavior per day with light physical activity was associated with a 1.47‐fold increase in the odds of maintaining cognitive function. An association between physical activity and cognitive function was not observed in female participants. Conclusions: Our results indicate that substituting sedentary behavior with light physical activity could be helpful in maintaining cognitive function in community‐dwelling oldest old men. These results highlight the importance of behavioral changes to promote cognition. Geriatr Gerontol Int 2020; 20: 773–778 .